FGR Diagnosis with EFW <10% versus AC <10%: Differences in Clinical Presentation, Pregnancy Outcomes, and Correlation with Placental Lesions of Malperfusion - Savage, Megan; Perez, Luiza; Nguyen, Natalie; Chasen, Stephen (American Journal of Perinatology, 2025)
This study aimed to identify what biometry is most predictive of placental malperfusion and obstetrical outcomes.Retrospective cohort study comparing pregnancies diagnosed with fetal growth restriction (FGR) from 2018 to 2020. Pregnancies with estimated fetal weight (EFW) < 10th percentile were characterized as the “EFW” group, and those with normal EFW but abdominal circumference (AC) < 10th percentile were characterized as the “AC” group. Mann–Whitney U, Fisher's exact test, and chi-square were used for statistical comparison.A total of 318 pregnancies were included, with 250 and 68 in EFW and AC groups, respectively. There were no significant differences in demographics between groups. The diagnosis was earlier in the EFW group (33 [30–36] vs. 35 [32–36] weeks; p = 0.001), with a higher proportion diagnosed at < 32 weeks. Delivery was also earlier in the EFW group (37 [35–38] vs. 38 [36–39] weeks; p = 0.01), with a higher rate of delivery <34 weeks compared with the AC group. Diagnosis at < 32 weeks was associated with higher rates of maternal (75.5 vs. 51.4%; p < 0.001) and fetal (25.5 vs. 14.6%; p = 0.02) malperfusion. After initial diagnosis, follow-up ultrasound was not consistent with FGR in 11.0% of cases, and this was more common in the AC group (19.1 vs. 8.7%; p = 0.03). “Resolution” of FGR was associated with lower rates of maternal malperfusion compared with persistent findings of FGR (28.5 vs. 63.3%; p < 0.001).In the cohort with FGR based on EFW <10th percentile, diagnosis and delivery were earlier. There was also a higher rate of delivery <34 weeks in the EFW group. There were no significant differences in the rate of placental lesions of maternal or fetal malperfusion based on diagnostic criteria of FGR however a diagnosis <32 weeks was associated with higher rates of malperfusion. Diagnosis based on small AC was more likely to “resolve” on follow-up and this was associated with lower rates of maternal malperfusion.
Keywords: fetal growth restriction; placental pathology; malperfusion; obstetrical outcomes